Performance Enhancement of Earth Air Heat Exchanger Systems through Geometric Modifications: A Comparative Study of Parallel, Series, and Modified Configurations - kumar Khare, Girish; Kumar Nikam, Sachin (Journal of Neonatal Surgery, 2025)
This study explores the thermal performance of an Earth Air Heat Exchanger (EAHE) system as a sustainable and passive cooling technology for building applications. Aluminum pipes buried beneath the ground were employed as the heat exchange medium, with simulations conducted using ANSYS Fluent and validated through field experiments in Gwalior, India, under hot and dry conditions. The novelty of this work lies in the comparative evaluation of three EAHE configurations—Parallel, Series, and a Modified design incorporating an outlet bend to improve airflow and heat exchange efficiency. Simulation models were calibrated with experimental results to ensure accuracy. The inlet air, initially at 42.5°C, was reduced to 29.5°C in the Parallel setup and 29.5°C in the Modified system, demonstrating cooling effects of up to 13°C. The Modified configuration showed the best agreement between simulation and experimental data, with minimal deviation (<2%) and superior thermal performance. This study emphasizes the role of geometric optimization in enhancing the effectiveness of EAHE systems. The outcomes offer practical insights for energy-efficient design strategies in tropical climates, where passive thermal comfort solutions are essential to reduce dependency on conventional HVAC systems.